The Predictive Value of Pre-plus Disease in Retinopathy of Prematurity - Wallace, David K. (2011)
OBJECTIVE: To determine the usefulness of pre-plus disease in predicting the need for laser treatment. METHODS: Posterior retinal video recordings were obtained during 710 indirect ophthalmoscopy examinations of 214 premature infants over a period of 5 years. Two masked experts reviewed short video recordings and determined whether there was plus, pre-plus, or neither. The primary analysis included results of one examination of the right eye at 33–34 weeks postmenstrual age (PMA). The primary outcome was a comparison of the proportion of eyes later requiring laser treatment between the group graded as pre-plus versus those graded as neither plus nor pre-plus disease. RESULTS: Of 10 eyes with pre-plus at 33–34 weeks PMA, 7 (70%) later required laser treatment; of 154 eyes without pre-plus or plus disease at 33–34 weeks, 14 (9%) later required laser treatment (risk ratio = 7.7; 95% CIs = 4.1, 14.8, p < 0.001). The mean time between the pre-plus examination and laser treatment was 1.6 (1.0–2.4) weeks. When adjusting for birth weight, gestational age, zone and stage, the presence of pre-plus at 33–34 weeks PMA independently predicted the need for laser treatment (adjusted odds ratio = 7.6, 95% CIs = 1.4, 42.3, p = 0.02). CONCLUSIONS: Pre-plus disease observed early in the course of ROP is strongly associated with the development of severe ROP requiring laser treatment. Pre-plus has prognostic value beyond that already provided by birth weight, gestational age, zone and stage. Eyes with pre-plus should be followed closely to allow optimal timing of intervention.